KEPEMIMPINAN DAN DISIPLIN KERJA : PENGARUHNYA TERHADAP KINERJA CADDIE : (Studi Kasus di PT. Taman Dayu Golf And Resort Pandaan – Pasuruan) - Andi Iswoyo; Wahyu Widi Astutik (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2014)
This study has aims to analyze the condition of Work Discipline, Communication skill and Caddie's Performance of PT. Taman Dayu Golf and Resort Pandaan Pasuruan, and analyze the effect of Work Discipline and Communication skill of employees toward Caddie's Performance of PT. Taman Dayu Golf and Resort Pandaan Pasuruan. The populations in this study were all caddies of PT. Taman Dayu Golf and Resort Pandaan Pasuruan with total of 124 peoples. The sample setting was using Slovin's formula by number of 56 and the technique of sample determination was using stratified random sampling. The variable in this study is Work Discipline (X1), Communication skill (X2) and Caddie's Performance (Y). The data analysis technique that used in this study is multiple linear regression analysis. And to test the research hypotheses was used a quantitative analysis through of regression model, F-test and t-test. The results showed that the average responses of respondents it was obtained the data that all the indicators of Work Discipline variable has values above of 3, so it can be concluded that the conditions of caddie's Work Discipline are well, and that all the indicators of Communication skill variable has values above of 3, so it can be concluded that the conditions of caddie's Communication skill are well, and the average response of respondents in this case the corporate leaders who assess the performance of caddie, it gained an average above of 3. So it can be concluded that the leader felt me performance of caddies are well. From the results of regression test and hypothesis test it was found that the work discipline and communication skill have significant effects on caddie's performance of PT. Taman Dayu Golf and Resort both of simultaneously and partially.